Questioning Skills Application on Analytical and Creative Thinking Skills of Pre Service Teacher - Widya Karmila Sari Achmad; Unga Utami; Nur Abidah Idrus (MIMBAR PGSD Undiksha, 2026)
The development of analytical and creative thinking skills is an essential competency in preparing pre service teachers to meet the demands of 21st century education. However, instructional practices in teacher education have not yet optimally fostered higher order thinking skills, highlighting the need for more effective pedagogical strategies. This study aims to analyze and evaluate the effect of the application of questioning skills on the analytical and creative thinking abilities of pre service teachers. The study employed a quasi-experimental non equivalent pretest posttest control group design involving pre-service teachers who were assigned to an experimental group and a control group. Data were collected using validated analytical thinking and creative thinking tests and were analyzed using Multivariate Analysis of Variance (MANOVA). The results revealed that the application of questioning skills had a significant effect on both analytical and creative thinking abilities. The intervention contributed 19.2% to the improvement of analytical thinking skills and 22.6% to creative thinking skills, indicating a greater effect on the development of creative thinking. These findings confirm that questioning skills constitute an effective pedagogical strategy for fostering higher order thinking skills. The study implies that systematically integrating questioning skills into teacher education programs can serve as a strategic approach to preparing reflective, adaptive, and innovative educators.